Perancangan Sistem Keamanan Ruang Server Akses Doorlock Dengan Teknologi RFID Berbasis IoT Pada Ruang Server FISIP UNJANI - Ade Sena Permana; Jumagar Arthady Sormin; Ni Ketut H.D (EPSILON: Journal of Electrical Engineering and Information Technology, 2022)
Security on the data server is needed to secure all data owned by an agency. The development of security access to the server room also needs to be improved to protect all data owned by the agency. This makes user-owned data sets very secure. In this study, researchers designed a security tool where users who access the server room must pass a doorlock based on IoT (Internet of Things). Security system doorlock uses RFID technology which is then processed by the raspberry accessed data to send the accessing data to the web server. The results of the design of a doorlock access server security system to the server room with IoT-based RFID technology in the NEW UNJANI project at a maximum distance of 2 cm between RFID tags and RFID with a 100% success rate of reading RFID reader to RFID tag. Further testing of RFID tags is given other media, namely wallets and cover cards whose tests get a 100% success percentage. With these results, the researcher again tested 3 RFID tags that have different types. Each RFID tag was tested 50 times, so that a total of 150 tests were carried out. For the first RFID tag , the failure percentage was 26%. For the second RFID tag , the failure percentage is 20%. For the third RFID tag , the success percentage is 100%.